Teste de memória de trabalho em libras: proposta e considerações - Nogueira, Newton da Rocha (2018)
The cognitive construct of working memory (hereafter MT) has been shown to be extremely relevant in the development and linguistic use, and there is evidence of an association between greater working memory capacity (henceforth CMT) and better performance in L2 (ORTIZPREUSS; SANZ, 2016). Most of these studies involve oral languages, but there is still a lack of research on the relationship between CMT and sign language performance. In addition, it is necessary to verify the functionality of the multicomponent MT model (BADDELEY, 2000) for sign language (CORINA; KNAPP, 2006; EMMOREY, et al., 2008), observing the role of each subsystem Phonological buffer, episodic buffer and visuospatial sketch). In view of this, the following research question arises: How could be a Work Memory test that adequately measures the storage and processing capacity of information in Libras (Brazilian Sign Language)? The present work aims to elaborate and evaluate a test in Libras, denominated of Libras span that aims to retain signals in order of appearance and at the same time to say if these signals involve or not during their realization. This test was applied to a group of users of Libras (deaf and hearing) and correlated with numerical-based MT tests, known as digit span whose task is to remember numbers in ascending order and operation span whose task is to solve calculations and remember the last digits of each operation. The purpose of this correlation was to evaluate the reliability and validity of the test with signals. Results showed that the Libras span task can become a good tool for assessing working memory capacity in Libras